2022
DOI: 10.3390/toxins14020112
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Mycotoxin Occurrence and Co-Occurrence in Croatian Cereals

Abstract: A total of 209 samples of various cereal crops (maize, wheat, barley, rye and oats) grown in Croatian fields during 2016 and 2017 were collected to analyze and determine the occurrence and co-occurrence of EU regulated mycotoxins in cereals (AFB1, AFB2, AFG1, AFG2, DON, FB1, FB2, ZEA, T-2, HT-2 and OTA). The analysis, performed by a validated confirmatory LC-MS/MS method based on a dilute and shoot principle, highlighted Fusarium mycotoxins as the main contaminants, often co-occurring in samples from both year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
5
14
0
Order By: Relevance
“…According to previous studies, it can be concluded that the highest contribution to AFM 1 in milk is due to contaminated corn, which is usually represented in the amount of 20-30% in feed concentrate used in the winter months for diet of dairy cow [18,58]. This is supported by a recently published study conducted for cereal samples from the 2017 harvest, which showed that corn samples were the most contaminated (8.7%) compared with wheat, barley, rye, and oat samples [59].…”
Section: Occurrence Of Afm 1 In Milkmentioning
confidence: 84%
“…According to previous studies, it can be concluded that the highest contribution to AFM 1 in milk is due to contaminated corn, which is usually represented in the amount of 20-30% in feed concentrate used in the winter months for diet of dairy cow [18,58]. This is supported by a recently published study conducted for cereal samples from the 2017 harvest, which showed that corn samples were the most contaminated (8.7%) compared with wheat, barley, rye, and oat samples [59].…”
Section: Occurrence Of Afm 1 In Milkmentioning
confidence: 84%
“…A total of 119 cereal samples from the 2016 harvest were analyzed during the cereal multi-contaminant investigation, revealing 8.5% of samples to be non-compliant with the relevant EU mycotoxin legislation, with Fusarium mycotoxin DON being the most frequently occurring (73.7%) [ 2 ]. In the study by Kovač et al (2022) [ 3 ] the method was used to analyze 209 cereal samples (maize, wheat, barley, oats, and rye) from 2016 and 2017 harvests from all Croatian counties, confirming the Fusarium mycotoxins as the main contaminants of Croatian cereals and revealing generally high mycotoxin co-occurrence in Croatian cereals (50.0% in 2016 and 33.7% in 2017), but also a correlation between year-to-year weather conditions and mycotoxin incidence, thus emphasizing the need for continuous mycotoxin control in a climate change-affected world.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this developed and validated UHPLC-MS/MS multi-mycotoxin method based on the dilute-and-shoot principle was successfully employed for EU-regulated mycotoxin determination in unprocessed cereal crops grown in Croatian fields, as already published by Kovač et al (2021;2022) [2,3]. A total of 119 cereal samples from the 2016 harvest were analyzed during the cereal multi-contaminant investigation, revealing 8.5% of samples to be non-compliant with the relevant EU mycotoxin legislation, with Fusarium mycotoxin DON being the most frequently occurring (73.7%) [2].…”
Section: Methods Performancementioning
confidence: 93%
See 2 more Smart Citations